1999
DOI: 10.1074/jbc.274.8.4816
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Containing High Density Lipoprotein Stimulates Endothelial Production of Heparan Sulfate Rich in Biologically Active Heparin-like Domains

Abstract: Reduced heparin and heparan sulfate (HS) proteoglycans (PG) have been observed in both inflammation and atherosclerosis. Methods to increase endogenous heparin and heparan sulfate are not known. We found that incubation of endothelial cells with 500 -1,000 g/ml high density lipoprotein (HDL) increased 35 SO 4 incorporation into PG by 1.5-2.5-fold. A major portion of this increase was in HS and was the result of increased synthesis. Total PG core proteins were not altered by HDL; however, the ratio of 35 SO 4 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 63 publications
4
30
0
Order By: Relevance
“…One explanation is that in transfected wells entrapment of secreted apoE by endothelial HSPG (32) may result in high local concentrations at the cell surface and enhanced biological activity. Indeed, HSPG is abundant on the cell-surface of cultured endothelial cells, and its production is rapidly stimulated by apoE (33). Although our transfection studies are not directly relevant to the situation in vivo, as endothelium does not synthesize apoE, they do have implications for gene therapy; transfecting endothelial cells to express apoE may limit endothelial activation.…”
Section: Fig 6 Apoer2 Is Expressed In Huvecsmentioning
confidence: 96%
“…One explanation is that in transfected wells entrapment of secreted apoE by endothelial HSPG (32) may result in high local concentrations at the cell surface and enhanced biological activity. Indeed, HSPG is abundant on the cell-surface of cultured endothelial cells, and its production is rapidly stimulated by apoE (33). Although our transfection studies are not directly relevant to the situation in vivo, as endothelium does not synthesize apoE, they do have implications for gene therapy; transfecting endothelial cells to express apoE may limit endothelial activation.…”
Section: Fig 6 Apoer2 Is Expressed In Huvecsmentioning
confidence: 96%
“…Many studies have now demonstrated that HDL apoE plays a crucial anti-atherogenic role. In vitro studies have shown that HDL apoE promotes cholesterol efflux from peripheral cells to the liver, 44 has a direct anti-atherogenic role at the site of atherosclerotic lesion, 45 has antioxidant activity 18 and inhibits platelet aggregation through the nitric oxide pathway. 46 In a previous work, we have also suggested that HDL apoE could play an anti-inflammatory role in vivo in obese adults.…”
Section: Discussionmentioning
confidence: 99%
“…ApoE also seems to be highly expressed in both MECA-367 ϩ HEV cells and MECA-79 ϩ HEV cells, but not in CD31 ϩ flat endothelial cells. Although ApoE is a ligand for several lipoprotein receptors and is known to play a major role in the hepatic clearance of remnant lipoproteins (45), it also stimulates the incorporation of 35 SO 4 and the production of heparan sulfate in endothelial cells (41). Because intensive incorporation of 35 SO 4 and production of heparan sulfate proteoglycans are observed in HEV cells in vivo (3), an increased expression of ApoE may be functionally related to the unique biosynthetic activity of HEV cells.…”
Section: Discussionmentioning
confidence: 99%
“…(10) and KC (36), an inflammatory cytokine, TAG7 (37), a promiscuous chemokine receptor, DARC (38), and some TGF-␤-responsive molecules, like mac25 (39), transglutaminase (40), and apolipoprotein E (ApoE) (41). Because these molecules are apparently not expressed in CD31…”
Section: Hev Cellsmentioning
confidence: 99%